Convergence of CO2 emissions in the selected world countries - Grodzicki, Tomasz; Jankiewicz, Mateusz (Bulletin of Geography. Socio-economic Series, 2023)
Nowadays, the topic of CO2 emissions has been a subject of intensive debate. There is a significant policy push toward reducing emissions that cause air pollution and other environmental concerns. The aim of this paper is to analyze the CO2 emissions as well as economic growth along with renewable energy use and the level of urbanization in the selected World countries in the period of 1995-2018. In general, almost all of the Northern part of the World was characterized by a high level of CO2 emissions, while the majority of African territory was the least polluted. The empirical result shows that the growth rate of air pollution is much higher in countries that initially had a low level of CO2 emissions, so the convergence process occurred. Conditioning convergence with the renewable energy use and the urbanization level indicates that its speed is higher. Club convergence analysis has proved that well-developed regions in terms of GDP per capita are able to improve the ecological situation despite further economic growth.